An analysis on the spatial heterogeneity characteristics of landscape ecological risk in Qilian Mountain National Park - Li, Yanlong; Qin, Qianqian; Wang, Duowen; An, Wanxiu; He, Xiaohui; Yu, Tianquan (Frontiers in Forests and Global Change, 2024)
As a key ecological functional area and a priority area for biodiversity conservation in China, the study of landscape ecological risks in Qilian Mountains National Park is of great significance in the context of the current national emphasis on ecological protection. In this research, based on land use data from six periods (i.e., year in 1995, 2000, 2005, 2010, 2015, and 2020) in the Qilian Mountains National Park， we used GIS and Fragstats to analyze the changes in land use and landscape pattern indices, and explored the spatial heterogeneity of ecological risk in Qilian Mountain National Park by constructing the ecological risk index. The results showed that: Grassland is the predominant land use type in the Qilian Mountains National Park. Notably, the area covered by woodland and grassland have exhibited a significant increase since 1995. Landscape fragmentation and disturbance indices exhibit fluctuations across different years, but showed an overall decreasing trend, and landscape stability was improved in the study area. There were obvious differences in the disturbance indices of different landscape types, with grassland and bare land having the highest values. Ecological risk in the study area is heterogeneous, with an overall low ecological risk and a shift to a lower risk level, and a decreasing trend in ecological risk, which is positively correlated spatially and mainly manifested as a "low-low" aggregation.